Catalytic Evaluation of an Optimized Heterogeneous Composite Catalyst Derived from Fusion of Tri-Biogenic Residues - Oyelayo Ajamu Oyedele; Simeon Olatayo Jekayinfa; Abass O. Alade; Christopher Chintua Enweremadu (Biomass)
This study analyzes the elemental and oxide compositions of three selected agricultural residues—Dried Pawpaw Leaves (DPL), Kola Nut Pod (KNP), and Sweet Orange Peel (SOP)—for their potential as heterogeneous catalysts. Energy Dispersive X-ray (EDX) analysis identified calcium (25%) and potassium (29%) as the primary elements in DPL and KNP, with calcium oxide (CaO) and potassium oxide (K2O) as the dominant oxides. SOP had a similar composition but lacked vanadium. Calcined residues were analyzed at temperatures ranging from 500 °C to 900 °C using X-ray Fluorescence (XRF), revealing stable silicon dioxide (SiO2) content and temperature-dependent variations in CaO and K2O, indicating their catalytic potential for transesterification processes. Scanning Electron Microscopy (SEM) showed non-uniform, spongy microstructures, enhancing the surface area and catalytic efficiency. Fourier Transform Infrared Spectroscopy (FTIR) identified functional groups essential for catalytic activity, such as hydroxyls, methyl, and carboxyl. X-ray Diffraction (XRD) confirmed the presence of crystalline phases like calcium carbonate and calcium oxide, crucial for catalytic performance. Experimental biodiesel production using a mixture of the calcined residues (33.33% each of KNPA, SOPA, and DPLA) resulted in the highest biodiesel yield at 65.3%. Model summary statistics, including R2 (0.9824) values and standard deviations (0.0026), validated the experimental design, indicating high precision and prediction accuracy. These results suggest that the selected agricultural residues, when calcined and mixed properly, can serve as effective heterogeneous catalysts, with significant implications for biodiesel production, supporting previous research on the importance of calcium in catalytic processes.